Endonucleolytic processing of CCA-less tRNA precursors by RNase Z in Bacillus subtilis - Pellegrini, Olivier (Oxford University Press, 2003)
In contrast to Escherichia coli, where the 3′ ends of tRNAs are primarily generated by exoribonucleases, maturation of the 3′ end of tRNAs is catalysed by an endoribonuclease, known as RNase Z (or 3′ tRNase), in many eukaryotic and archaeal systems. RNase Z cleaves tRNA precursors 3′ to the discriminator base. Here we show that this activity, previously unsuspected in bacteria, is encoded by the yqjK gene of Bacillus subtilis. Decreased yqjK expression leads to an accumulation of a population of B.subtilis tRNAs in vivo, none of which have a CCA motif encoded in their genes, and YqjK cleaves tRNA precursors with the same specificity as plant RNase Z in vitro. We have thus renamed the gene rnz. A CCA motif downstream of the discriminator base inhibits RNase Z activity in vitro, with most of the inhibition due to the first C residue. Lastly, tRNAs with long 5′ extensions are poor substrates for cleavage, suggesting that for some tRNAs, processing of the 5′ end by RNase P may have to precede RNase Z cleavage.